Potensi Aplikasi Endofit dalam Agroekosistem Berkelanjutan: Biofertilizer dan Biokontrol Hayati - Sihotang, Saipul; Panggabean, Ellen Lumisar; Alifyah, Nabila; Saragih, Nur Betty; Nasution, Lita; Halawa, Emmanuel; Saragih, Ryan (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2025)
Endophytic microorganisms have become a central focus in numerous studies related to sustainable agriculture due to their dual potential as biological agents—functioning both as biocontrol and biofertilizers. The presence of endophytes within plant tissues has been shown to enhance vegetative growth, strengthen resistance against pathogenic attacks, and optimize nutrient uptake. This article presents a systematic review of recent studies from 2018 to 2024, addressing the classification, mechanisms of action, and potential applications of endophytic microorganisms in agriculture. Several bacterial genera, including Bacillus spp., Azospirillum spp., and Pseudomonas spp., along with non-pathogenic fungal groups such as Trichoderma spp. and Fusarium spp., have demonstrated effectiveness in nitrogen fixation, phosphate solubilization, phytohormone synthesis, and the production of antimicrobial compounds. Research findings indicate that the application of endophytic microorganisms as biological inputs holds great promise in supporting the development of environmentally friendly, sustainable, and high-yielding agricultural systems.